2020
DOI: 10.3897/phytokeys.154.49615
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of Schizanthus Ruiz & Pav. (Solanaceae), a genus endemic to the southern Andes

Abstract: We present a taxonomic synopsis of the South American genus Schizanthus Ruiz & Pav. (Solanaceae), within which we recognise seventeen taxa (14 species with three infraspecific taxa). The genus is mainly distributed in Chile between the coast of the Atacama Desert and the southern temperate forests, while two species occur in the Argentinian Provinces of Mendoza and Neuquén. This taxonomic treatment is based on the analysis of herbarium specimens from 30 different herbaria. For each accepted species we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Specific status based on recent studies and reports published after April 2019 (not included in Palchetti et al, 2020 ) has been considered. This included studies, such as the revision of the genus Schizanthus ( Morales-Fierro et al, 2020 ; Lavandero et al, 2021 ); updates in Nolana ( Hepp and Dillon, 2018 ); the Morelloid clade of Solanum in Argentina ( Knapp et al, 2020 ); cryptic species recently reported ( Moreira-Muñoz and Muñoz-Schick, 2020 ); and new Petunia and Nicotiana species ( Greppi et al, 2019 ; Santilli et al, 2021 ). After a first cleaning, data from ex situ living collections that introduced species, hybrid taxa, and records with doubtful or incomplete identification at the species level were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Specific status based on recent studies and reports published after April 2019 (not included in Palchetti et al, 2020 ) has been considered. This included studies, such as the revision of the genus Schizanthus ( Morales-Fierro et al, 2020 ; Lavandero et al, 2021 ); updates in Nolana ( Hepp and Dillon, 2018 ); the Morelloid clade of Solanum in Argentina ( Knapp et al, 2020 ); cryptic species recently reported ( Moreira-Muñoz and Muñoz-Schick, 2020 ); and new Petunia and Nicotiana species ( Greppi et al, 2019 ; Santilli et al, 2021 ). After a first cleaning, data from ex situ living collections that introduced species, hybrid taxa, and records with doubtful or incomplete identification at the species level were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…However, the authors only cited collections in Chilean herbaria, which does not rule out the possibility that specimens as old or even much older might be found in European or US herbaria. Morales-Fierro et al (2020) revised the genus Schizanthus Ruiz & Pav. (Solanaceae) in Chile.…”
Section: Another Overlooked Species In the Chilean Floramentioning
confidence: 99%